Photo-biomodulatory response of low-power laser irradiation on burn tissue repair in mice. Issue 9 (December 2016) - Rathnakar, Bharath; Rao, Bola; Prabhu, Vijendra; Chandra, Subhash; Rai, Sharada; Rao, Anuradha; Sharma, Mrinalini; Gupta, Pradeep; Mahato, Krishna
Abstract The present work reports the photo-biomodulatory effect of red (632.8 nm) and near infrared (785 and 830 nm) lasers on burn injury in Swiss albino mice. Animals were induced with a 15-mm full thickness burn injury and irradiated with various fluences (1, 2, 3, 4, and 6 J/cm2 ) of each laser wavelength under study having a constant fluence rate (8.49 mW/cm2 ). The size of the injury following treatment was monitored by capturing the wound images at regular time intervals until complete healing. Morphometric assessment indicated that the group treated with 3-J/cm2 fluence of 830 nm had a profound effect on healing as compared to untreated controls and various fluences of other wavelengths under study. Histopathological assessment of wound repair on treatment with an optimum fluence (3 J/cm2 ) of 830 nm performed on days 2, 6, 12, and 18 post-wounding resulted in enhanced wound repair with migration of fibroblasts, deposition of collagen, and neovascularization as compared to untreated controls. The findings of the present study have clearly demonstrated that a single exposure of 3-J/cm2 fluence at 830-nm enhanced burn wound healing progression in mice, which is equivalent to 5 % povidone iodine treatment (reference standard), applied on a daily basis till complete healing.